Improved Synthesis and Chromophoric Properties of Tetra-b-(2-octanyloxy)substituted Nickel Phthalocyanine - Cong, Fangdi; Wang, Haifeng; Li, Jianxin; Li, Lingling; Yan, Qianyun; Chu, Xinxin; Meng, Yanyan; Xing, Kezhi; Du, Xiguang (Asian Journal of Chemistry, 2014)
In order to further apprehend chromophoric properties of phthalcyanine materials, a lipophilic tetra-b-(2-octanyloxy)-substituted nickel phthalocyanine was synthesized with a yield of 78 % by a facile method without nitrogen protection and long-term heating performance. The synthetic compound was characterized by mass spectra, 1H NMR, UV-visible, IR and elemental analysis, which were consistent with the proposed molecular structure. The compound not only behaved excellent solubility in many organic solvents, but also exhibited different chromophoric properties in various types of solvents, e.g., blue in isooctane and green in tetrahydrofuran. More interestingly, the chromophoric properties could be largely modulated by employed solvent, solution concentration and environment temperature.